Characterizing cryptic species: A morphometric analysis of craniodental characters in the dwarf galago genus Galagoides. Issue 2 (14th July 2015) - Masters, Judith C.; Couette, Sébastien
ABSTRACT Objectives The true dwarf galagos of the genus Galagoides, G. demidoff and G. thomasi, are difficult to distinguish morphologically at a specific or subspecific level, and most taxonomic designations are based primarily on geographic localities. We used morphometrics to investigate the morphological diversity of the genus. Materials and Methods We conducted statistical analyses of 12 linear measurements on 290 Galagoides skulls housed in museums worldwide, and assembled body weights for 71 wild caught specimens. We examined sexual dimorphism and specific and subspecific distinctiveness using MANOVA, ANOVA, principle components analysis and canonical variate analysis. Results We distinguished skulls identified as Galagoides demidoff and G. thomasi with ∼70% reliability, and demonstrated consistently different patterns of static allometry in craniodental variables. Variables supporting specific distinction included M1 width, palate width at P2, palate (snout) length, length of premaxillary tube, width across mastoids, and total skull length. The type specimens of G. orinus and G. rondoensis were significantly different from G. demidoff and G. thomasi, but grouped with them in a CVA including G. zanzibaricus and G. granti, although molecular studies indicate that their true affiliation is with the latter species. Subspecies within G. demidoff could not be distinguished using craniodental morphometrics. Discussion Galagoides demidoff and G. thomasi can be distinguished relatively reliably, and are broadly sympatric across western and central Africa. Neither species showed evidence of sexual dimorphism in craniodental size or shape. Size variation has a greater influence on skull morphology in G. demidoff than it has on G. thomasi. Am J Phys Anthropol 158:288–299, 2015. © 2015 Wiley Periodicals, Inc.